Oncolytic Vaccinia Virus Armed with GM-CSF and IL-7 Enhances Antitumor Immunity in Pancreatic Cancer - Wenyi Yan; Yujing Xuan; Ruimin Wang; Ziyan Huan; Yu Guo; Huilin Dun; Lihua Xu; Ruxia Han; Xianlei Sun; Lingling Si; Nicholas Robert Lemoine; Yaohe Wang; et al. (Biomedicines)
Objectives: Pancreatic cancer remains a therapeutic challenge due to its immunosuppressive microenvironment and treatment resistance. This study aimed to develop a novel recombinant oncolytic vaccinia virus (VVL-GL7) co-expressing granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin-7 (IL-7), designed to enhance anti-tumor immunity and synergize with immune checkpoint inhibitors. Methods: VVL-GL7 was constructed through CRISPR/Cas9-mediated knockout of TK and A49 genes, combined with the simultaneous insertion of dual cytokine-encoding cassettes. Anti-tumor efficacy was evaluated in vitro and in vivo using C57BL/6 mouse and Syrian hamster pancreatic cancer models. Comprehensive immune profiling evaluated CD8+ T-cell and macrophage infiltration dynamics while simultaneously assessing memory T-cell differentiation patterns using flow cytometry. Preclinical combination studies of VVL-GL7 and the PD-1 immune checkpoint inhibitor were systematically evaluated in a syngeneic pancreatic cancer model. Results: VVL-GL7 exhibited potent oncolytic activity, inducing significant tumor regression in both preclinical models. VVL-GL7 therapy significantly augmented CD8+ T-cell and macrophage infiltration within the tumor microenvironment, while concomitantly driving memory T-cell differentiation. The synergistic effects of VVL-GL7 and the PD-1 blockade further improved therapeutic outcomes, resulting in significantly higher tumor remission rates compared to monotherapy and achieving complete tumor regression in pancreatic cancer models. Conclusions: VVL-GL7 reprograms the immunosuppressive tumor microenvironment and synergizes with anti-PD-1 antibodies to overcome resistance in pancreatic cancer.